Foraging behaviour and habitat partitioning of two sympatric cormorants in Patagonia, Argentina - Frere, Esteban (2008)
Radiotelemetry was used to assess the distribution and diving behaviour of Rock Shags Phalacrocorax magellanicus and Red-legged Cormorants Phalacrocorax gaimardi breeding in sympatry, and Rock Shags breeding in isolation. When breeding in sympatry there was little overlap in the foraging locations of the two species, with the highest densities of each species separated by 10 km. Red-legged Cormorants fed significantly closer to the breeding colony than did Rock Shags and undertook shorter foraging trips, making almost twice as many foraging trips per day as Rock Shags. Rock Shags breeding in isolation had a shorter foraging range than the birds breeding in sympatry with Red-legged Cormorants and foraging trip duration was significantly shorter. However, the number of feeding trips per day was similar between areas of sympatry and allopatry. Differences in the foraging ecology of Rock Shags in areas of sympatry and allopatry may be due to interspecific competition, which forces niche differentiation. The distance between foraging sites, the speed of movement of the prey, a species tendency to move into prey-depleted areas and the length of the breeding season (during which the birds are constrained to be in the same area) may play critical roles in determining the extent to which differential area use by competitors is a strategy that benefits both parties.